Real particle physics analysis by UK secondary school students using the ATLAS Open Data: an illustration through a collection of original student research - Conroy, E; Barr, A; Harris, Y; Kirk, J; Olaiya, E; Phillips, R (Springer, 2024)
Since the 2020 release of 10fb-1 of integrated luminosity of proton–proton collision data to the public by the ATLAS experiment, significant potential for its use for youth engagement in physics and citizen science has been present. In particular, this article aims to address whether, if provided adequate training and resources, high school students are capable of leveraging the ATLAS Open Data to semi-autonomously develop their own original research projects. To this end, a repository of interactive Python Jupyter notebook training materials was developed, incrementally increasing in difficulty; in the initial instalments no prior knowledge of particle physics or Python coding is assumed, while in the latter stages students emulate the steps of a real Higgs boson search using ATLAS data. This programme was implemented in secondary schools throughout the UK during the 2022/23 academic year and is presented in this article through a collection of research projects developed by a selection of participating students.